2018
DOI: 10.3390/molecules23040980
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Polylactide (PLA) and Its Copolymers

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Among other filaments, FDM technology allows for additive manufacturing of biopolymers such as lignin and polylactides (PLA), a biodegradable filament used for tissue engineering purposes in various fields of regenerative medicine and dentistry [24][25][26]. Despite environmental advantage in terms of biodegradability, recent studies showed improvements of the mechanical properties by changing the layups of the fibers of subsequent layers [20].…”
Section: Introductionmentioning
confidence: 99%
“…Among other filaments, FDM technology allows for additive manufacturing of biopolymers such as lignin and polylactides (PLA), a biodegradable filament used for tissue engineering purposes in various fields of regenerative medicine and dentistry [24][25][26]. Despite environmental advantage in terms of biodegradability, recent studies showed improvements of the mechanical properties by changing the layups of the fibers of subsequent layers [20].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating two monomers with different physicochemical properties in one copolymer is of great interest, especially for biomedical applications. Copolymerization brings the advantages and properties of both monomers into one macromolecular structure, and several copolymers have already been synthesized and used for biomedical applications [ 28 , 36 , 37 , 38 , 51 , 52 , 53 , 54 ]. Since we have previously shown the effectiveness of the 1-pyreneacetic acid/P 4 - t -Bu initiator/base system for the homopolymerization of both diMeMLABn & diMeMLAHe, the same initiator/base system has been selected to polymerize sequentially diMeMLAHe and diMeMLABn in two ratios allowing to modulate the hydrophobic/hydrophilic balance of the final amphiphilic block copolymers ( Scheme 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…in which X is the OD 600 value, which describes the biomass concentration, μ m is the maximum specific growth rate (h −1 ), and X m is the maximum OD 600 . l-Lactic acid production was described by the Luedeking-Piret function [20] = + (2) in which P is the l-lactic acid concentration (g/L), α is a growth-associated constant, and β is a non-growthassociated constant.…”
Section: Kinetic Modelsmentioning
confidence: 99%
“…In recent years, the urgent need to reduce environmental pollution caused by plastics has driven the development of biodegradable green plastics. Polylactic acid (PLA), a type of environmentally friendly plastic, has attracted unprecedented global attention owing to its biodegradable and biocompatible properties; it has the potential to replace traditional plastics produced by petroleum fuels [1][2][3]. Some properties of PLA, including its crystallinity, thermal stability and hydrolysis resistance, are affected by the relative fractions of l-and d-isomers in polymer chains [4][5][6].…”
Section: Introductionmentioning
confidence: 99%